A quiet strength - Oke, Janette, 1935- (Minneapolis, Minn. : Bethany House, 1999)
Virginia Simpson looks forward to a quiet married life with Jonathan but trials and disappointments await as she tries to balance relationships in her household.
Accelerated Reader AR
Keywords: Christian fiction